Leadership Skills for Entrepreneurs: An Analytical Study for the Reality of Entrepreneurship in the Sultanate of Oman - Al Hamdi, Khalefa (The Arab Journal of Administration, 2023)
The study exposes the reality of entrepreneurship in the Sultanate of Oman by reviewing the institutional frameworks that enable Entrepreneurship sector to play its primary role in local economic development and foster the potentials of the knowledge economy. It also discussed the key challenges faced by entrepreneurship by examining international and local official reports. The researcher relied on the analytical-inductive method to address the study topic. One of the primary findings indicated that Oman places significant emphasis on entrepreneurship throughout different institutions and sectors. The past decade, showed a profound transformation in economic and legislative reforms pertaining to the entrepreneurship sector. However, the attention devoted to developing the skills and behaviors of individuals involved in this sector has not kept up with the pace of economic and legislative changes. The researcher recommended establishing specialized research centers in order to diagnosing issues, anticipating future challenges, and addressing them accordingly. Furthermore, it is essential to concentrate on leadership skills related to entrepreneurship through diverse approaches. The study also highlighted the importance of reassessing the teaching methodologies in schools and universities concerning entrepreneurial ambitions, and leveraging innovative and more effective marketing tools to attract young individuals to participate in this sector.